2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Social Security and Medicare [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The purpose of Social Security and Medicare is to provide social benefits to qualified workers who retire, become disabled, and/or require medical assistance. This is EDIS document FE415, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.